Presiding Judge Mario Olmos Keynotes Fresno County Bar Association Luncheon re Court Filings - Watkins, Howard::::::::: (1989)
Fresno Municipal Court Assistant Presiding Judge Carl Evans also noting increases in case filings and need for more Pro Tem Judges